“Let Me Breathe of It”: A Circumpolar Literary and Ecological Perspective - Athens, Allison K. (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (University of New Brunswick, Dept. of English, 2014)
The commercial hunting of harp seal pups galvanized animal rights in the 1970s, culminating in the banning of sealskin products in Europe and the curtailment of trade in the United States. The seal in animal rights discourse is a type of object that needs saving in the form of protective measures to keep her safe from the rapacious greed of capitalism. However, in Indigenous discourse, the seal is another relative, a relation whose presence makes all certainties about hierarchy, use-value, moral exemption, and human exceptionalism impossible. This essay re-thinks the figural dimensions of seals in Yupiit and Inuit storytelling practices alongside debates around over-harvesting, competing global interests, and animal rights to develop current activism for environmental justice for both humans and seals in a time of rapid change. I suggest that focusing on practices of care rather than commodity circulation reframes the relationship of humans and seals beyond binary systems of interpretation that make humans subjects (with “culture”) and seals objects (in “nature”). Inuit stories, legal statutes, and environmental conservation rhetoric all appear to be different, if not contradictory, types of narratives. Nevertheless, when read together, they reveal a shared ethics of care for the wellbeing of the seal. This care, I suggest, momentarily frees seals from their entrapment in an economy of use and provides a basis for understanding the North as a lived environment.